Programmed Cell Death Protein 1-overexpressed CD8+ T Lymphocytes Play a Role in Increasing Chronic Hepatitis B Disease Progression - Fatmawati Fatmawati; Ellyza Nasrul; Nasrul Zubir; Ferry Sandra (The Indonesian Biomedical Journal, 2021)
BACKGROUND: T lymphocyte activation depends on the balance of co-stimulatory and co-inhibitory signals determined by Cluster of Diffrentiation (CD)28 and Programmed Cell Death Protein 1 (PD-1) expression. Alteration in CD28 and PD-1 expression might affect the progression of chronic hepatitis B (CHB). Current study was conducted to evaluate the correlations of the CD28 and PD-1 expressions of T lymphocytes and CHB progression.METHODS: Subjects were recruited, selected and divided into 3 groups, inactive CHB, active CHB and CHB with End-Stage Liver Disease (ESLD). HBeAg was determined by using Enzyme-Linked Fluorescence Assay while HBV-DNA was carried out by the RT-PCR method. Numbers of T lymphocytes expressing CD3, CD4, CD8, CD45, CD28 and PD-1 molecules were determined by flowcytometry. RESULTS: There was no significant difference in the expression of CD28 by CD4+ and CD8+ T lymphocytes of inactive CHB, active CHB and CHB with ESLD subjects. There was also no significant difference in the expression of PD-1 in CD4+ lymphocytes of inactive CHB, active CHB and ESLD subjects. In contrast there was a significant increase in the expression of PD-1 in CD8+ T lymphocytes of ESLD subjects.CONCLUSION: CD28 expression among CHB subjects was within normal range and not related to disease progression, but PD-1 expression of CD8+ T lymphocyte was increased along with disease progression, especially in CHB subjects with ESLD. This suggests that PD-1-overexpressed CD8+ T lymphocyte play a role in increasing CHB disease progression.KEYWORDS: chronic hepatitis B, CD28, PD-1, T lymphocyte, disease progression